2023
DOI: 10.1159/000529409
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Treatment Regimen on the Initial Management of Macular Neovascularization Subtypes in Age-Related Macular Degeneration

Abstract: OBJECTIVE: To evaluate the effect of initial treatment regimen individualization, (Pro Re nata (PRN) or Treat-and-Extend (TAE)), according to macular neovascularization (MNV) subtype, on the functional and anatomical response in neovascular age-related macular degeneration (nAMD). The secondary objective is to compare the treatment burden between each MNV subtypes. METHODS: Consecutive treatment-naïve nAMD patients were retrospectively included. MNV subtype was graded by 2 independent blinded investigators on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Other studies have shown different distributions of the CNV subtypes, with subtype 1 found in 34-61% of eyes and subtype 3 in 2-40% of eyes [22,[25][26][27]. The predominance of type 1 CNV in our study is in accordance with the recent publications by Mathis et al [28,29]. These eyes might need a higher number of injections [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have shown different distributions of the CNV subtypes, with subtype 1 found in 34-61% of eyes and subtype 3 in 2-40% of eyes [22,[25][26][27]. The predominance of type 1 CNV in our study is in accordance with the recent publications by Mathis et al [28,29]. These eyes might need a higher number of injections [30,31].…”
Section: Discussionsupporting
confidence: 91%